Analisis Manajemen Persediaan Bahan Baku Pada UMKM Rengginang Berlian Kriuk di Karawang - Cherilya Alfara Natasya; Lilis Fitriyani; Putri Ayu Rukmini; Siti Santi; Ujang Suherman (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to determine the most effective inventory management in Rengginang Berlian Kriuk MSMEs. Using a qualitative descriptive approach, researchers analyze inventory management in Rengginang Berlian Kriuk MSMEs. The problem in this research is that Rengginang Berlian Kriuk MSMEs have not implemented raw material inventory management. The results of interview observations and documentation show that inventory management at Rengginang Berlian Kriuk MSMEs is not optimal. This is indicated by the minimal inventory available, because there are limitations in managing inventory. For this reason, researchers use safety stock and EOQ techniques to analyze inventory which can support inventory management effectively and efficiently.